Quality of Life in Patients with Alopecia Areata presenting to the Department of Dermatology at a Tertiary Care Hospital of Lahore, Pakistan - Aisha Ahmad, Zahida Perveen, Madiha Zulfiqar, Shaista Umbreen, Zartaj Liaqat, Mariam Saeed, Haseeb Mehmood Qadri (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Alopecia Areata (AA), also known as spot baldness is thought to be autoimmune in origin, marked by patchy, non-scarring hair loss. More recently, a strong association between the sufferers of AA and disorders of mood disturbances, anxiety and depression has been noted. Aim: To determination the mean quality of life score in patients with alopecia areata (AA). Study design: Prospective, cross-sectional study. Place and duration: Department of Dermatology, Jinnah Hospital, Lahore from March 2021 to September 2021. Methodology: After ethical approval, we included 124 patients irrespective of their gender aged between 18-60 years presenting with AA in this study after informed consent. Patient’s demographic details were noted. Quality of life was assessed using Dermatology Life Quality Index (DLQI) score. Results: Of the total 125 patients, about 59.2% patients were male and 40.8% females, with a mean of 29.72±11.01 years. The mean duration of disease was 9.45±8.56 months. DLQI score ranged from 2 to 24 with a mean of 6.74±4.60. When stratified, DLQI score was significantly higher among females (p=0.008), those with disease duration >12 months (p=0.000) and severe disease (p=0.024). Conclusion: This study found that AA is associated with deterioration of quality of life of patients and the effect is more marked among female patients and those with more severe and chronic disease. Key-words: alopecia areata, quality of life, dermatology, autoimmune disease